Impact of long-term nutrient management on soil quality under cluster bean-wheat cropping system in hyper arid region - KUMAWAT, SURESH; KHARIA, S.K.; YADAV, S.R.; SHEKHAWAT, P.S.; PAREEK, N.K. (Journal of Soil and Water Conservation, 2024)
Organic and inorganic nutrients are important for crop productivity and soil health. A field experiment was started in 2008 under All India Co-ordinated Research Project in western Rajasthan to study the long-term effects of nutrient management strategy using Soil Test Crop Response approach on cluster bean- wheat cropping system. The present investigation indicated effects of organic compost and inorganic fertilizer as per soil test crop response approach basis on soil quality. The treatments consisted of General recommended dose (T1), Target yield 15 q ha-1 (T2), Target yield 15 q ha-1 with IPNS (T3), Target yield 20 q ha-1 (T4) and Target yield 20 q ha-1 with IPNS (T5). The soil organic pools were studied after 9 years and it was found that application of with 20 q ha-1 with IPNS(T5) increased significantly available phosphorus, Potassium, dehydrogenase activity, urease activity, fluorescein diacetate activity and alkaline phosphatase activity, total porosity of soil and moisture retention of soil and decrease in soil bulk density, Infiltration rate and hydraulic conductivity while total sulphur content maximum recorded under target yield 20 q ha-1 (T4) in different soil depth.